Staged Hybrid Endovascular Repair of a Ruptured Abdominal Aortic Aneurysm with Aortocaval Fistula - Chung, Sandra A (Aorta (Stamford), 2015)
There is a growing body of literature expanding the indication of endovascular aneurysm repair, from prophylactic treatment of aneurysms to other indications such as ruptured and complicated ruptured abdominal aneurysms. Concomitant aortocaval fistula is rare, and reports of open and endovascular repair exist. We report a unique hybrid approach to a case of a ruptured abdominal aortic aneurysm with aortocaval fistula, repaired primarily via endovascular approach in a hybrid, two-staged fashion. Representative images are presented in addition to a short review of this pathology.